Penguatan Perilaku Hidup Sehat dan Bermoral melalui Edukasi Anti-Narkoba, Anti-Bullying, dan Anti-Korupsi - Ekawati Rini Wulansari; Luluk Hermawati; Ghea Farmaning Thias Putri; Rifdah Hanifah; Ainina Al Shadrina; Dwi Widyawati (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
Early character education plays a fundamental role in shaping a generation that is not only intelligent but also physically healthy, emotionally balanced, and morally responsible. The cultivation of these values from an early age is crucial to equip children with the resilience needed to face various social challenges in the future. This community service activity was designed to increase awareness among elementary school students regarding three critical issues: the dangers of drug abuse, the practices of bullying, and the detrimental impact of corruption. The program was conducted at SDN 1 Citeluk with the participation of approximately 80 students from grades IV to VI. The educational materials were delivered through an interactive approach combining lectures, group discussions, role-playing, and quizzes. This approach was selected to ensure that the learning process was enjoyable, engaging, and easily understood by children at the elementary school level. During the sessions, students were introduced to the basic concepts of drugs, their harmful effects on health and life, and the importance of avoiding them. Additionally, the program emphasized identifying the various forms of bullying—whether physical, verbal, or social—and encouraged students to develop empathy and mutual respect. Another important aspect addressed was corruption, where students were guided to recognize the value of honesty and integrity through relatable examples in daily life. The results of the activity revealed that students were able to clearly understand the dangers of drugs, recognize the different forms of bullying, and provide examples of honest and moral behavior. This indicates that early character education delivered through interactive and participatory methods can effectively enhance children’s comprehension of healthy and moral values. It is expected that similar programs can be carried out sustainably in elementary school settings as part of continuous character-building efforts to support the development of a responsible and ethical young generation